Digital elevation model workflow improvements for the MarsSI platform and resulting orthorectified mosaic of Oxia Planum, the landing site of the ExoMars 2022 rover. (1st November 2022) - Volat, Matthieu; Quantin-Nataf, Cathy; Dehecq, Amaury
Abstract: In this publication, we explore the options to improve the quality and speed of DEM generation procedures from stereo-photogrammetry pipeline of the MarsSI online service. We study available algorithms, options and workflows. Taking inspiration on earth-based work, we propose a new workflow relying on the semi-global matching algorithms and a two steps approach with the result of artifacts/noise reduction in the products, and improved co-registration of the outputs. We use this new workflow in the production of mosaic of ground models and orthorectified images. We illustrate the pipeline with the example of the othorectified HiRISE images mosaic that has been used in the framework of Exomars project to perform a join mapping of Oxia Planum, the landing site of Exomars rover. Highlights: Describes the new DEM workflow of the MarsSI platform. Noise and artifact levels were improved. Alignment to MOLA was improved, enough to consider automated CTX mosaics. ESA ExoMars 2022 landing site covering DEM and orthorectified image datasets.